2019
DOI: 10.3390/vetsci6040092
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Molecular Characterization of a Natural Coinfection of Marek’s Disease Virus and Reticuloendotheliosis Virus in Brazilian Backyard Chicken Flock

Abstract: Marek’s disease virus (MDV) and the reticuloendotheliosis virus (REV) are two of the primary oncogenic viruses that significantly affect chickens. In Brazil, there have been no previous published reports on the presence of field REV alone or in coinfection. This retrospective study analyzes samples from a case of lymphoproliferative lesions from a backyard chicken flock. MDV and REV were detected by PCR and classified as MDV1 and REV3, respectively, through sequencing and phylogenetic analysis based on the gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
2
13
0
2
Order By: Relevance
“…Similarly, the atypical clinical manifestations of FP (Back et al, 1995;Hess et al, 2011;Sentíes-Cué et al, 2010) could be explained by the contribution of REV in the pathology of these birds. All these results indicate that REV arrived in Brazil and South America several years ago, as was previously reported (Canal & Corrêa, 2009;Chacón et al, 2019), as well as other parts of the world (Kim & Tripathy, 2001). These findings highlight the importance of monitoring for REV in the poultry industry because its immunosuppressive effects may be masked by other opportunistic or coinfecting infectious agents.…”
Section: Microscopic Pathology Findings Revealed Typical Cellular Lessupporting
confidence: 86%
See 2 more Smart Citations
“…Similarly, the atypical clinical manifestations of FP (Back et al, 1995;Hess et al, 2011;Sentíes-Cué et al, 2010) could be explained by the contribution of REV in the pathology of these birds. All these results indicate that REV arrived in Brazil and South America several years ago, as was previously reported (Canal & Corrêa, 2009;Chacón et al, 2019), as well as other parts of the world (Kim & Tripathy, 2001). These findings highlight the importance of monitoring for REV in the poultry industry because its immunosuppressive effects may be masked by other opportunistic or coinfecting infectious agents.…”
Section: Microscopic Pathology Findings Revealed Typical Cellular Lessupporting
confidence: 86%
“…Positive controls included a commercial vaccine (Poximune ® AE, Ceva Animal Health) for FPV and a liver sample from a previously confirmed bird with REV (Chacón et al., 2019). Skin from specific pathogen‐free (SPF) chickens resuspended in 1.5 ml of phosphate‐buffered saline (PBS) was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For many years, an increase in the pathogenicity of MDV strains has been observed despite immunoprophylaxis being used in day-old chicks. Such an increase was observed as early as 1997 in the vaccinated flocks of birds ( 3 , 4 ).…”
Section: Discussionmentioning
confidence: 91%
“…Investigations in Brazil also confirmed that MDV infection is a significant problem. In addition, double infection with MDV and reticuloendotheliosis virus was diagnosed in samples from a flock from the vicinity of San Paulo ( 4 ). Birds from this flock had not been vaccinated against Marek’s disease.…”
Section: Discussionmentioning
confidence: 99%